The secrets of fashion drawing : an insider's guide to perfecting your creative skills - Chapman, Noel; Cheek, Judith (Arcturus, 2015)
Drawing is the primary skill for anyone considering a career in fashion design. The Secrets of Fashion Design is a down-to-earth yet inspiring insight into aspects of drawing and illustration for this exclusive sector. Peeking behind the scenes to discover how the industry works, this book: addresses the language of fashion, its origins and uses, takes a fascinating trip through the world of color, examining its significance in fashion, explores drawing styles and presentation methods, and features the experiences and inspirations of real-life fashion professionals.